The Quality of Life in Heart Failure Reduced Ejection Fraction (HFrEF) Patients: A Phenomenon of Obesity Paradox - Yogi Puji Rachmawan; Witri Pratiwi; Helda Helda (GHMJ (Global Health Management Journal))
Background: Obesity place patients at risk of cardiovascular disease (CVD). There may be an inverse relationship between obesity and CVD prognosis-a phenomenon known as the “obesity paradox”. Obese HF patients might have a better prognosis, especially in terms of quality of life (QoL).